Flaws in foldamers: conformational uniformity and signal decay in achiral helical peptide oligomers1. Issue 4 (16th April 2015) - Le Bailly, Bryden A. F.; Byrne, Liam; Diemer, Vincent; Foroozandeh, Mohammadali; Morris, Gareth A.; Clayden, Jonathan
<x xml:space="preserve">Abstract</x> The conformational influence of a single stereogenic centre in an otherwise achiral oligomer behaves as a signal that decays with distance.